Covid-19 and Sarcopenia: A bibliometric analysis - Vaishya, Raju; Gupta , Brij Mohan; Singh , Yogendra; Vaish , Abhishek (Iberoamerican Journal of Science Measurement and Communication, 2023)
Objective. Covid-19 disease affects all organs of the human body, including muscles. However, the association between Covid-19 and Sarcopenia has not been analyzed bibliometrically. In this study, we performed a bibliometric analysis to identify the current hotspots and highlight future trends. Design/Methodology/Approach. The Scopus database was used as a data source. We analyzed the following indicators: document type, country, collaboration patterns, affiliation, journal name, and citation patterns. MS-Excell and VOSviewer were employed to map and determine essential topics in this field. Results/Discussion. 846 publications were retrieved from Scopus. They have received 15651 citations, averaging 18.5 citations per paper (CPP). 29.43% of publications received extramural funding from international agencies and together registered a CPP of 40.66. The USA published the most significant number of publications (n=162). However, the highest CPP and Relative Citation Index (RCI) was registered by China (186.0 and 10.05). “Medicine” contributed the largest global output share (82.98%). The Sapienza Università di Roma, Italy (n=20) was the most productive institution. Whereas, Deutsches Zentrum für Herz-Kreislauf-Forschung e. V. Germany registered the highest CPP and RCI. F. Landi was the most impactful author. The International Journal of Environmental Research and Public Health (n=38) and Nutrients (n=28) were the most productive journals. The most prevalent topics of research, as reflected in keywords by frequency of their appearance, were “Covid-19” (n=810), “Sarcopenia” (n=324), “Skeleton Muscle” (n=309), “Muscle Mass” (n=214), “Grip Strength” (n=199), “Physical Activity” (n=172). Conclusions. This bibliometric study revealed that papers on ‘Covid-19 and Sarcopenia” received a high number of citations (average of 18.5 CPP) within a short period. Those papers which got external funding received much higher CPP (40.66). Maximum contributory and impactful authors were from High-Income Countries. The highly cited papers were 5.25% of the total publications.